2020
DOI: 10.3390/molecules25061356
|View full text |Cite
|
Sign up to set email alerts
|

Engineered ZnO and CuO Nanoparticles Ameliorate Morphological and Biochemical Response in Tissue Culture Regenerants of Candyleaf (Stevia rebaudiana)

Abstract: Sustainable production of secondary metabolites in medicinal plants by artificial culturing on the industrial scale has gained worldwide importance. Engineered nanoparticles (ENPs) play a pivotal role in the elicitation of compounds of medicinal value. This investigation explores the influence of ZnO and CuO ENPs on in vitro roots formation, non-enzymatic antioxidant activities, and production of steviol glycosides (SGs) in regenerants of Candyleaf, Stevia rebaudiana. ENPs were applied in 0, 2, 20, 200, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 55 publications
1
34
0
Order By: Relevance
“…A comparative study of NPs effects is the enhance of α-tocopherol in vitro production of Argan using TiO 2 NPs and Silicon Dioxide (SiO 2 ) NPs as elicitors are reported in both NPs a concentration of 5 ppm with SiO 2 NPs as mayor effect (4.59 and 4.7 fold of the control respectively) [73]. Ahmad et al [69] studied ZnO and CuO NPs elicitation in candy leaf; they reported an increase of rebaudioside A (4.42%), stevioside content (1.28%), total phenolic content (5.86 µg gallic acid equivalent/mg), total flavonoid content (6.25 µg QE/mg), total antioxidant activity (9.09 µg AAE/mg), total reducing power (11.04 µg AAE/mg) and % DPPH inhibition (75.6%) treatment with 2 mg/L of ZnO. Under the elicitation of CuO NPs, the authors reported an increment of total phenolic content (4.55 µg gallic acid equivalent/mg), total flavonoid content (5.67 µg QE/mg), total antioxidant activity (10.05 µg AAE/mg), total reducing power (12.04 µg AAE/mg) and % DPPH inhibition (75.6%) treatment with 20 mg/L [69].…”
Section: Nutraceuticals and Nutritional Compounds Induction Using Npsmentioning
confidence: 99%
“…A comparative study of NPs effects is the enhance of α-tocopherol in vitro production of Argan using TiO 2 NPs and Silicon Dioxide (SiO 2 ) NPs as elicitors are reported in both NPs a concentration of 5 ppm with SiO 2 NPs as mayor effect (4.59 and 4.7 fold of the control respectively) [73]. Ahmad et al [69] studied ZnO and CuO NPs elicitation in candy leaf; they reported an increase of rebaudioside A (4.42%), stevioside content (1.28%), total phenolic content (5.86 µg gallic acid equivalent/mg), total flavonoid content (6.25 µg QE/mg), total antioxidant activity (9.09 µg AAE/mg), total reducing power (11.04 µg AAE/mg) and % DPPH inhibition (75.6%) treatment with 2 mg/L of ZnO. Under the elicitation of CuO NPs, the authors reported an increment of total phenolic content (4.55 µg gallic acid equivalent/mg), total flavonoid content (5.67 µg QE/mg), total antioxidant activity (10.05 µg AAE/mg), total reducing power (12.04 µg AAE/mg) and % DPPH inhibition (75.6%) treatment with 20 mg/L [69].…”
Section: Nutraceuticals and Nutritional Compounds Induction Using Npsmentioning
confidence: 99%
“…Therefore, the application of SNP may pave the way for obtaining somatic embryogenesis or improving organogenesis protocols in cannabis. Recent studies showed that adding nanoparticles to the culture media improves callogenesis, organogenesis, somatic embryogenesis, and rhizogenesis by inhibiting the production of ROS and ethylene and altering gene expression and antioxidant enzyme activities [ 100 , 101 , 102 , 103 , 104 , 105 ]. Thus, the application of nanoparticles can be investigated as a promising approach to enhance the in vitro regeneration capacity of cannabis.…”
Section: In Vitro Culture In Cannabismentioning
confidence: 99%
“…Seeds of S. rebaudiana show poor germination and the conventional propagation strategies such as cuttings are not effective [5]. Hence, new biotechnological approaches have been adopted for maximum production of Stevia progeny and its medicinal components in the minimum period of time [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%